Enhanced electron field emission from NiCo2O4 nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Materials Research Express, 2015)
Electron emission properties of electrodeposited spinel NiCo2O4 nanosheet arrays grown on Ni foam have been studied. The work function of NiCo2O4 was calculated by density functional theory using the plane-wave basis set and used to estimate the field enhancement factor. The NiCo2O4 nanosheet arrays exhibited a low turn-on field of 1.86 V mu m(-1) at 1 mu A cm(-2) and current density of 686 mu A cm(-2) at 3.2 V mu m(-1), with field enhancement factor beta = 1460 and good field emission current stability. The field emission properties of the NiCo2O4 nanosheet arrays showed enhanced performance compared to chemically prepared NiCo2O4 nanosheets. Hence, the nanosheet arrays have great potential as robust high performance vertical structure electron emitters for future flat panel displays and vacuum electronic device applications.
Keywords: Density functional theory; field emission; nanosheets; NiCo2O4; spinel

Enhanced field emission of plasma treated multilayer graphene - Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2015)
Electron emission properties of multilayer graphene (MLG) prepared by a facile exfoliation technique have been studied. Effect of CO2 Ar, N-2, plasma treatment was studied using Raman spectroscopy and investigated for field emission based application. The CO2 plasma treated multilayer graphene shows an enhanced field emission behavior with a low turn on field of 0.18 V/mu m and high emission current density of 1.89 mA/cm(2) at an applied field of 0.35 V/mu m. Further the plasma treated MLG exhibits excellent current stability at a lower and higher emission current value. (C) 2015 AIP Publishing LLC.

Effect of plasma treatment on multilayer graphene: X-ray photoelectron spectroscopy, surface morphology investigations and work function measurements - Patil, Urmila V.; Pawbake, Amit S.; Machuno, Luis G. B.; Gelamo, Rogerio V.; Jadkar, Sandesh R.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report here the effect of plasma treatment on multilayer graphene samples as determined by X-ray photoelectron spectroscopy and surface morphology studies with atomic force microscopy, scanning electron microscopy and transmission electron microscopy. The plasma treatment was modified to introduce controlled levels of defects and functionalities to the graphene samples to give tunable properties. The elemental composition and structure were investigated by XPS and micro Raman spectroscopy. The XPS study showed that there was a slight variation in the sp(2)/sp(3) hybridization ratio between the plasma-treated samples and the pristine sample. Kelvin probe measurements were carried out on all the multilayer graphene samples and indicated a slight variation in the work function of the graphene samples after plasma treatment.